A survey of dietary supplements choices and preferred forms of supplement use by Malaysian athletes - Hisham, Nurul Izzati Mohd (2021)
The main aim of this study is to investigate the type of dietary supplements, the reason for taking a supplement and the most preferred forms of supplement use by athletes during exercise. Another specific objective of this study is to examine the type of dietary supplement, consumed by athletes during exercise, the factors of taking the supplement among athletes during exercise, and to identify the most preferred forms of supplement (e.g., tablets, capsules, powder, gummies, fluids, or nutrition bars) and reason for choosing their favoured form of supplements among athletes during exercise. The participants were asked to complete an online interview that consisted of three parts: physical fitness level, supplement use, and the most favoured form of supplement ingestion. Each session took around 15 minutes for each participant to complete their responses to the questions. For the participants who cannot join Webex sessions due to their tight schedule or poor internet connection, they need to fill up a google form using the shared link. Every answer was noted on the answer sheet, while the answers on the survey link were downloaded and the answers were grouped into specific keywords and were analysed. Correlation and stepwise regression were used for statistical analysis. A total of 138 participants from state and national athletes from various sports were joining this online interview. There are 61 footballers, 11 hockey players, 14 track and field athletes, 32 rugby players and 20 from other sports such as basketball, netball and softball who are joining this research. These research findings shown 87 athletes were actively training more than 3 days per week with a mean average was 3.61 ± 1.74 days per week. While 51 athletes were doing exercise or training less than 3 days per week with a mean average of 2.01 ± 1.28 days per week. The association between physical activity with supplements intake and side effects had a significant negative association (r= -0.28, p= 0.001) and (r= -0.20, p= 0.019) respectively. Besides that, the preferred form of supplements intake had a significant association with physical activity (r= 0.18, p= 0.034). Using stepwise regression analysis, reason on choosing the form of the supplement was the best predictor of favoured form supplement intake which accounted for 5.2%. and adjusted R2 was -0.015. However, the results showed that liquid forms of supplements were the most preferred form by the participants. The results were influenced by the reason that had been given by the participants which are to enhance fitness level other than it is easy to be carried and consumed.